Penggunaan Mainan “Spider Fidget Mathic” pada Siswa Kelas 3 MI Tarbiyatul Huda - Alvianita, Mahda; Aisyah, Azizah Nur; Ananda, Romadhona Regita (JAMU : Jurnal Abdi Masyarakat UMUS, 2024)
Learning media props convey information about learning and deliver learning material. Learning media should be conceptualized as customized toys that are innovated into learning toys that are close to children's characteristics, methods and learning styles. Because the stimulus chosen for elementary school children should be contextual, interesting, and preferably contemporary so as to stimulate students' curiosity so that they can achieve better learning outcomes. Community service activity on October 25 2022 at MI Tarbiyatul Huda Jombang Regency as an activity to implement the use of learning media in the form of the "Spider Fidget Mathic" toy in the learning process in understanding numeration in basic multiplication operation material. Which aims to help students increase the understanding, enthusiasm and ability of Grade 3 MI students to increase their potential in understanding numeracy based on the material studied. Students use learning media in the form of the "Spider Fidget Mathic" toy. The results of this service activity show that the use of "Spider Fidget Mathic" in class 3 MI makes children better and more enthusiastic in learning activities, making it easier for students to understand material that previously used lecture and conventional methods. Because learning using the "Spider Fidget Mathic" toy increases students' understanding, active learning, enthusiasm for learning, and cognitive abilities.